Pengaruh Harga, Promosi dan Citra Merek Terhadap Keputusan Pembelian Konsumen Pada Perumahan Bale Agung Pemalang - Setya Pramono (International Forum of Researchers and Lecturers, 2023)
This type of research is an explanatory study, with a population of around 100 respondents who are interested in buying a house in Bale Agung Pemalang Housing. The sample collection uses non-probability sampling. The sampling technique used purposive. Data collection was carried out through a questionnaire. Methods of data analysis using correlation, regression, using the SPSS application. This study concludes that price, promotion and brand image have an effect on purchasing decisions, both partially and stimulantly, the price variable has a greater influence than the promotion variable.